Family-School Synergy Model: Linking Home Environment and Learning Motivation to Social Studies Achievement in Elementary Schools - Sri Mekarni; Alfroki Martha; Weni Yulastri (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
This study aimed to examine the individual and simultaneous effects of family environment and learning motivation on Social Studies learning outcomes among elementary school students at SD Negeri 67/III Lubuk Paku, Kerinci Regency, Jambi Province, Indonesia. A quantitative approach with a causal associative research design was employed, involving 60 students selected through total sampling. Data were collected using validated questionnaires measuring family environment and learning motivation, alongside official end-of-semester academic score documentation. Multiple linear regression analysis was conducted using IBM SPSS Statistics version 25. Results revealed that family environment (β = 0.369, p less than 0.05) and learning motivation (β = 0.465, p less than 0.05) each exerted a significant positive effect on Social Studies learning outcomes, with both variables jointly explaining 61.0% of outcome variance (R² = 0.610, F = 44.873, p less than 0.001). Learning motivation emerged as the comparatively stronger predictor. These findings underscore the theoretical contribution of integrating self-determination theory within the rural Indonesian elementary school context and carry direct practical implications: teachers are recommended to implement autonomy-supportive instruction and formative feedback practices to strengthen students' intrinsic motivation, while parents are encouraged to establish structured home-learning routines, provide adequate learning resources, and improve the quality of academic communication with their children as foundational supports for Social Studies achievement.